Knowledge, Attitude and Practices regarding Hepatitis B and C among Paramedics - Husnain, Hafiz Maoz; Mehmood, Bilal; Waqar, Sidra Anwar; Arif, Tayyab (Infectious Diseases Journal of Pakistan, 2023)
Background: Hepatitis B and C is not uncommon in healthcare workers. We aim this study to determine the baseline knowledge regarding causation, transmission and prevention of hepatitis B and C in health care persons. We also would like to observe the current clinical practices of paramedics regarding prevention of transmission of HBV and HCV from one patient to other. Methods: This cross-sectional study involving 45 paramedics was conducted in Allied hospital Faisalabad in duration of one month from January 2017 to February 2017. Each respondent was asked about their relevant personal health history and their knowledge and practices regarding the occurrence, transmission and prevention of hepatitis B and C. chi-square test were used to determine the association between level of practices and knowledge. Results: Out of 45 paramedics, 6 (13.4%) were having average knowledge regarding hepatitis B and C and remaining 39 (86.6%) participants had good knowledge. All participants know that blood transfusion, shaving razors and use of infected surgical/ medical instruments are definitive sources of transmission of these infections. All participants were aware that use of separate new syringe for every patients helps to prevent the transmission of these infections. 88.9% paramedics had the habit of discarding the syringe after use. Only 40% dispensers had the habit of wearing gloves before doing any invasive procedure. Level of practice regarding prevention of HBV and HCV infection was good in only 26.6% dispensers, average in 53.3% dispensers and poor in 20.0% dispensers. There was no significant difference in level of practice in preventing the transmission of infection in dispensers who have good knowledge about hepatitis B and C and those having average knowledge (p-value 0.53). Conclusion: The practice level of paramedics regarding prevention of hepatitis B and C virus transmission is average and only onethird of the paramedics follow good practices regarding prevention of hepatitis B and C virus infection. Key Words: Hepatitis B virus, Hepatitis C virus, Paramedics.